2016
DOI: 10.4038/sljb.v1i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of physical and cooking quality characters of selected traditional and improved rice varieties in Sri Lanka

Abstract: Several physical and cooking quality parameters of fifteen traditional and nine hybrid rice varieties were analyzed. All the tested parameters showed significance variations (p<0.05) irrespective of being traditional or hybrid varieties. The highest equivalent diameter was observed in Devaraddiri while lowest was recorded for Sudurusamba. The mean kernel volume values ranged from 4.08±0.01-20.54±0.13 mm 3 . The highest kernel length of 6.82 mm was observed in At 305 and the lowest value of 3.6 mm was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 13 publications
1
27
0
Order By: Relevance
“…According to Thomas, Wan-Nadiah, and Bhat [ 4 ], physical properties are evaluated to provide important facts in determining their appropriate uses. Bulk density was inversely related to the L : W ratio, round grain showed the highest bulk density, and slender grain showed the lowest [ 21 – 23 ]. Similar findings were seen in this experiment, from the principle component analysis, we can conclude that bulk density and grain breadth are positively correlated and negatively correlated with length-breadth ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Thomas, Wan-Nadiah, and Bhat [ 4 ], physical properties are evaluated to provide important facts in determining their appropriate uses. Bulk density was inversely related to the L : W ratio, round grain showed the highest bulk density, and slender grain showed the lowest [ 21 – 23 ]. Similar findings were seen in this experiment, from the principle component analysis, we can conclude that bulk density and grain breadth are positively correlated and negatively correlated with length-breadth ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Cooking time is also related to the amylose content and varied significantly among the varieties [ 5 ]. Hettiarachchi et al [ 21 ] reported in their study that variation in the cooking time among different varieties could be related to the gelatinisation temperature; however, some varieties with a high gelatinisation temperature have shown low cooking time. In this study, landrace like Aanga has a high gelatinisation temperature which has shown the longest cooking time and Chiniya has shown the lowest cooking time and has a low gelatinisation temperature.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study also confirmed that At 405 was prone to more structural damage during milling due to its basmati characteristics. According to the grain size and shape, Bg 360 and At 405 were categorized as short-bold and extra along-slender type grains respectively [8]. Low-amylose rice flour of At 405 may cause less resistance to shear force and a simultaneous increase in the starch damage during the dry milling.…”
Section: Discussionmentioning
confidence: 99%
“…Although Sri Lanka has developed many improved rice varieties named as Bg (≈43 varieties), Bw (≈16 varieties), Ld (≈8 varieties) and At (≈17 varieties), about 99% of them can be classified as highintermediate amylose rice. According to the available data, only At 405 can be classified as commercialized low-amylose rice variety [6,7,8]. The amylose content of the rice starch directly affects the cooking and sensory properties of rice [7,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation